Leadership therapy inside the mind of Microsoft - Rowley, Anna (Palgrave Macmillan, 2007)
Microsoft is well-known for being an intense place to work: employees face constant pressure to innovate and excel and are passionately devoted to their jobs. In this insightful book, Anna Rowley reveals the major problems all managers face and shows how to conquer them. She distills the characteristics every leader must have to succeed in a demanding environment, including belief, confidence, self-awareness, trust, power, and ambition. She provides the tools that have helped her clients to continue to attain their potential, while including fascinating case studies of the driven and talented clients she has worked with at Microsoft.